Effective contamination control strategies facilitating axenic cultivation of Haematococcus pluvialis: Risks and challenges. (January 2022) - Yu, Byung Sun; Lee, So Young; Sim, Sang Jun
Graphical abstract: Highlights: Commercial use of H. pluvialis to produce astaxanthin and ω-3 FA has been reviewed. Possible contaminations in different cultivation systems are discussed. Biological pollutant species and their contamination modes are presented. Decontamination technologies according to biocontaminants are introduced. Further cost-effective strategies on controlling the contaminants are necessary. Abstract: With industrialization, anthropogenic mishandlings have resulted in the discharge of abundant amount of CO2 into the atmosphere. This has triggered an unnatural warming that has dramatically increased the Earth's temperature in a short duration. This problem can be addressed by the biological conversion of CO2 ; several studies have been conducted using H. pluvialis culture that produces high value-added materials, such as astaxanthin and omega-3 fatty acids. However, although H. pluvialis has a high market value, the market size is quite small. Because H. pluvialis cells are susceptible to contamination due to its slow growth rate, hence large-scale culture of H. pluvialis without reliable contamination control strategies poses significant risks. This review comprehensively discusses the contamination that occurs during the culturing of H. pluvialis in various culture systems under different culture conditions. The review also discusses the strategies in controlling the biotic contaminants, such as bacteria and fungi.